High Efficiency Computation of the Variances of Structural Evolutionary Random Responses - J.H. Lin; D.K. Sun; W.X. Zhong; W.S. Zhang (Shock and Vibration)
For structures subjected to stationary or evolutionary white/colored random noise, their various response variances satisfy algebraic or differential Lyapunov equations. The solution of these Lyapunov equations used to be very difficult. A precise integration method is proposed in the present paper, which solves such Lyapunov equations accurately and very efficiently.